The Role of Heme Oxygenase-1 in Remote Ischemic and Anesthetic Organ Conditioning - Inge Bauer; Annika Raupach (MDPI AG, 2019)
The cytoprotective effects of the heme oxygenase (HO) pathway are widely acknowledged. These effects are mainly mediated by degradation of free, pro-oxidant heme and the generation of carbon monoxide (CO) and biliverdin. The underlying mechanisms of protection include anti-oxidant, anti-apoptotic, anti-inflammatory and vasodilatory properties. Upregulation of the inducible isoform HO-1 under stress conditions plays a crucial role in preventing or reducing cell damage. Therefore, modulation of the HO-1 system might provide an efficient strategy for organ protection. Pharmacological agents investigated in the context of organ conditioning include clinically used anesthetics and sedatives. A review from Hoetzel and Schmidt from 2010 nicely summarized the effects of anesthetics on HO-1 expression and their role in disease models. They concluded that HO-1 upregulation by anesthetics might prevent or at least reduce organ injury due to harmful stimuli. Due to its clinical safety, anesthetic conditioning might represent an attractive pharmacological tool for HO-1 modulation in patients. Remote ischemic conditioning (RIC), first described in 1993, represents a similar secure option to induce organ protection, especially in its non-invasive form. The efficacy of RIC has been intensively studied herein, including on patients. Studies on the role of RIC in influencing HO-1 expression to induce organ protection are emerging. In the first part of this review, recently published pre-clinical and clinical studies investigating the effects of anesthetics on HO-1 expression patterns, the underlying signaling pathways mediating modulation and its causative role in organ protection are summarized. The second part of this review sums up the effects of RIC.